Sikap Wanita Infeksi Menular Seksual tentang Keputihan - I Dewa Ayu Ketut Surinati; Ni Nyoman Hartati (Jurnal Gema Keperawatan, 2016)
This study purpose to determine the attitude of sexually transmitted infections in women of leukorrhea. This type of research is descriptive. With cross sectional approach, The sampling technique used consecutive sampling technique in selecting the sample 30. The results Based on the attitude of 18 people (60%) have a positive attitude and negative attitude as much as 12 respondents (40%).